Update on pharmacotherapy for stroke and traumatic brain injury recovery during rehabilitation. Issue 6 (December 2016) - Liepert, Joachim
Abstract : Purpose of review: This article evaluates whether specific drugs are able to facilitate motor recovery after stroke or improve the level of consciousness, cognitive, or behavioral symptoms after traumatic brain injury. Recent findings: After stroke, serotonin reuptake inhibitors can enhance restitution of motor functions in depressed as well as in nondepressed patients. Erythropoietin and progesterone administered within hours after moderate to severe traumatic brain injury failed to improve the outcome. A single dose of zolpidem can transiently improve the level of consciousness in patients with vegetative state or minimally conscious state. Summary: Because of the lack of large randomized controlled trials, evidence is still limited. Currently, most convincing evidence exists for fluoxetine for facilitation of motor recovery early after stroke and for amantadine for acceleration of functional recovery after severe traumatic brain injury. Methylphenidate and acetylcholinesterase inhibitors might enhance cognitive functions after traumatic brain injury. Sufficiently powered studies and the identification of predictors of beneficial drug effects are still needed.